Cilacap’s Volleyball Club Coaching (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Volleyball is one of the most popular team sports in the world, characterized by explosive movement, fast and nimble position, jumping and blocking. Coaching a club is very important to achieve goals,namely achievement. Thus, it became the background for the researcher researched volleyball clubs in Cilacap Regency. This research used a qualitative approach namely problem discussed which was aimed to describe or show situations based on a complex order, a holistic picture, data collection technique s using observation, interview, and documentation. The object of this research was Pelindo Cilacap, men’s and women’s Imigrasi Volleyball Club, Bea Cukai Volleyball Club, men’s and women’s Pertamina Volleyball Club, men’s and women’s Holcim Volleyball Club, Polres Volleyball Club, and Pemda Volleyball Club.The results of the research conducted on coaching volleyball clubs in Cilacap Regency, they are: 5 men’s Volleyball clubs (Pelindo, Imigrasi, Bea Cukai, Pertamina and Holcim men's club). Then, 5 women's Volleyball clubs namely, Pertamina, Holcim, Pemda, Polres, and Imigrasi. However, there are only 2 clubs, that are still active in the formation of players, namely, men’s and women’s Pertamina volleyball clubs and then men’s and women’s Holcim volleyball clubs. Coaching is focused on the city while the Cilacap area is wide, and distance has a huge influence, the need for structured coaching for junior athletes. Facilities and infrastructure owned by the club in the form of outdoor grass and sandy fields, do not yet have an indoor field. The indoor court of Cilacap Regency government is not used by the clubs for volleyball training. Additionally, the condition of Wijayakusuma’s Hall is also inadequate in terms of stands and lighting.